2016
DOI: 10.3390/healthcare4030053
|View full text |Cite
|
Sign up to set email alerts
|

The Development of a Mindfulness-Based Music Therapy (MBMT) Program for Women Receiving Adjuvant Chemotherapy for Breast Cancer

Abstract: Problems with attention and symptom distress are common clinical features reported by women who receive adjuvant chemotherapy for breast cancer. Mindfulness practice significantly improves attention and mindfulness programs significantly reduce symptom distress in patients with cancer, and, more specifically, in women with breast cancer. Recently, a pilot investigation of a music therapy program, built on core attitudes of mindfulness practice, reported significant benefits of enhanced attention and decreased … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
23
0
2

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(25 citation statements)
references
References 31 publications
0
23
0
2
Order By: Relevance
“…Our focus was on one component of mindfulness programs—attentional control—which we speculated could be beneficial in managing worries that may arise following stroke and in improving attention and concentration that may be impaired following stroke. Mindfulness‐based music therapy has recently been shown to enhance mood and attention in women with breast cancer receiving adjuvant chemotherapy . Further work is needed to determine whether mindful music listening can reduce the likelihood of developing anxiety/depression and improve attention poststroke, but the comments from our participants are promising.…”
Section: Discussionmentioning
confidence: 94%
See 1 more Smart Citation
“…Our focus was on one component of mindfulness programs—attentional control—which we speculated could be beneficial in managing worries that may arise following stroke and in improving attention and concentration that may be impaired following stroke. Mindfulness‐based music therapy has recently been shown to enhance mood and attention in women with breast cancer receiving adjuvant chemotherapy . Further work is needed to determine whether mindful music listening can reduce the likelihood of developing anxiety/depression and improve attention poststroke, but the comments from our participants are promising.…”
Section: Discussionmentioning
confidence: 94%
“…Mindfulness-based music therapy has recently been shown to enhance mood and attention in women with breast cancer receiving adjuvant chemotherapy. 25,26 Further work is needed to determine whether mindful music listening can reduce the likelihood of developing anxiety/depression and improve attention poststroke, but the comments from our participants are promising.…”
Section: Discussionmentioning
confidence: 99%
“…Recently, attempts have been made to combine mindfulness and music, such as the mindfulness-based music therapy program. 34 In Korea, however, few studies have used music meditation in the elderly group. 35 In the future, MM programs for the elderly, especially for the middle-old or oldest-old, may be designed including music components.…”
Section: Discussionmentioning
confidence: 99%
“…The research has shown that although both cognitive and embodied forms of knowledge are necessary in the development of therapeutic presence, embodied knowledge is currently a neglected epistemological paradigm in the majority of educational and healthcare settings (Geller & Greenberg, 2012;Henry, 2010;Kontos & Naglie, 2009;Medcalf, 2017). However, the researcher would again like to state that this may not be the case in all music therapy educational programs, as there are currently many mindfulness-based music therapy programs already being integrated into music therapy practices (Lesiuk, 2016;Rynex, 2018). In relation to developing therapeutic presence as a student music therapist and incorporating meditative and embodied practice into music therapy programs, experiential learning has great potential to provide an educational framework, discussed further by Murphy (2007, pp.…”
Section: Discussionmentioning
confidence: 99%